Karakteristik dan Profil Asam Lemak Kombinasi Minyak Ikan Patin dan Minyak Hati Ikan Hiu: Characteristics and Fatty Acid Profile of Catfish and Shark Liver Oil Mixture - M Lamudin Noor; Andarini Diharmi; Rahman Karnila (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2021)
Catfish oil is rich in omega-9 fatty acids but low in omega-3 fatty acids. Meanwhile, shark liver oil has a relatively high omega 3 fatty acids content. This study was aimed to determine the characteristics and chemical properties of catfish oil and the fatty acid profile of the catfish oil and shark liver mixture. TBbelly fat of catfish was extracted by dry rendering resulting crude and purified oil. The refined catfish oil ismixed with shark liver oil with a ratio of 1: 1, 2: 1 and 2: 1. The analysis parameters consisted of chemical characteristics (free fatty acid, acid value, peroxide, iodine, p-anisidine, saponification, total oxidation/TOTOX), and fatty acid profile. The results showed that the combination of catfish oil and shark liver produced free fatty acids ranging from 1.59-2.19%, acid number 2.86-3.00 mg KOH/g peroxide value15.50-18.32 meq/kg, iodine number 63.46- 84.42 gI2/100g), p-anisidin value 21.53-24.16, saponification 142.21-162,28 mg KOH/g, and TOTOX 53.33-69.43. Palmitic acid, oleic acid, and linoleic acid were the most dominant saturated, monounsaturated and polyunsaturated fatty acid, respectively. The chemical properties meet the IFOMA's standards. The combination of shark liver oil and catfish with a ratio (2:1) resulted in the highest content of omega-3 (0.65%) and omega-6 (29.75%).